UNSTABLE EARLY-HOLOCENE CLIMATIC AND ENVIRONMENTAL CONDITIONS IN NORTHWESTERN RUSSIA DERIVED FROM A MULTIDISCIPLINARY STUDY OF A LAKE-SEDIMENT SEQUENCE FROM PICHOZERO, SOUTHEASTERN RUSSIAN KARELIA - Wohlfarth B.; Brunnberg L.; Schwark L.; Bennike O.; Filimonova L.; Tarasov P.; Björkman L.; Demidov I.; Possnert G. (My University, 2004)
A sediment core from Lake Pichozero (61°46'; N, 37°25'; E 118m a.s.l.) provides information on the environmental and climatic conditions in southeastern Russian Karelia during the Lateglacial and early Holocene (12 800-9300 cal. BP). The chronology of the sequence is constrained by varve counting and AMS 14C measurement of terrestrial plant macrofossils. Multiproxy analyses (magnetic susceptibility, grain size, TOC, TN, TS, Rock Eval, pollen and macrofossils) imply that cold and dry regional climatic conditions with sparse Arctic vegetation prevailed prior to 11500 cal. BP. Coincident with the transition to the Holocene at 11 500 cal. BP, air temperatures and lake productivity increased and Betula pubescens and Populus tremula started to migrate into the area, followed by Picea abies at 10 750 cal. BP. Although lake productivity decreased at around 11 000 cal. BP and remained low until 9600 cal. BP, pollen-based climate reconstructions imply variable climatic conditions in the region over time. Drier and colder summers prevailed from ∼11 200 to 10 900 cal. BP, followed by an interval of higher annual temperatures and precipitation from 10 900 to 10 750 cal. BP. Lower annual temperatures and drier conditions existed from 10 750 to 10 200 cal. BP, and higher temperatures and precipitation are inferred between 10 200 and 10 000 cal. BP. Finally, declining temperatures and precipitation occurred from 10 000 cal. BP onwards, with a minimum at around 9600 cal. BP. These climatic shifts are temporally coincident with those recorded in North Atlantic terrestrial, marine and ice-core archives and indicate that relatively minor climate signals were transmitted further to the east.
Keywords: Northwestern Russia; Lateglacial; early Holocene; multiproxy study; palaeoenvironment; palaeoclimate; lacustrine sediments; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен